2008
DOI: 10.1144/sp306.1
|View full text |Cite
|
Sign up to set email alerts
|

Potential mechanisms for the genesis of Cenozoic domal structures on the NE Atlantic margin: pros, cons and some new ideas

Abstract: Abstract:The mild compressional structures of Cenozoic age on the passive margins bordering Norway, the UK, the Faroes and Ireland have been the subject of much discussion in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
109
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(113 citation statements)
references
References 82 publications
1
109
0
3
Order By: Relevance
“…Doré & Lundin 1996;Japsen & Chalmers 2000;Lundin & Doré 2002;Ritchie et al 2003;Gomez & Verges 2005;Doré et al 2008;Stoker et al 2010;Tuitt et al 2010;Japsen et al 2012;Yamato et al 2013;Døss-ing et al 2016). Cenozoic compressional domes have been described on the Vøring, Faroe -Shetland and Hatton margins, in the Rockall Basin (for a short summary see Kimbell et al 2016), and in the NE Greenland margin (Price & Whitham 1997;Hamann et al 2005).…”
Section: Subduction In the Pacific And Mediterranean Realms And The mentioning
confidence: 99%
See 1 more Smart Citation
“…Doré & Lundin 1996;Japsen & Chalmers 2000;Lundin & Doré 2002;Ritchie et al 2003;Gomez & Verges 2005;Doré et al 2008;Stoker et al 2010;Tuitt et al 2010;Japsen et al 2012;Yamato et al 2013;Døss-ing et al 2016). Cenozoic compressional domes have been described on the Vøring, Faroe -Shetland and Hatton margins, in the Rockall Basin (for a short summary see Kimbell et al 2016), and in the NE Greenland margin (Price & Whitham 1997;Hamann et al 2005).…”
Section: Subduction In the Pacific And Mediterranean Realms And The mentioning
confidence: 99%
“…Doré et al 2008; and see the summary in Kimbell et al 2016). Previous studies have postulated a range of possible causes for post-break-up compression along the NE Atlantic margins, and they range from, for example, ridge-push and gravity potential forces, mantle convection (including small-scale convection along passive margins), far-field stresses, and differential compaction (for a comprehensive review see Doré et al 2008).…”
Section: Subduction In the Pacific And Mediterranean Realms And The mentioning
confidence: 99%
“…As is well known, the World Stress Map (Heidbach et al 2008) shows that the current orientation of principal horizontal stress is less related to the direction of rifting than to the current direction of plate motion, giving present-day and presumably therefore palaeocompressive stresses at oblique angles to the margins. The relationship of such plate motion-induced stresses, or body-force stresses associated with plate boundaries, to observed strain phenomena is discussed in the paper by Doré et al (2008). Broad compression-related folds in the CretaceousCenozoic cover successions are observed over a wide area between the Mid-Norwegian shelf and the Rockall-Faroes area.…”
Section: Subtle Migration Pathsmentioning
confidence: 99%
“…West of the Helland-Hansen Arch is the Mogdunn Arch (Fig. 1), and further south are the South Modgunn Arch, the Havsule Dome and the Isak Dome: all of these structures were active in the Miocene (Blystad et al 1995;Lundin & Doré 2002;Doré et al 2008). Doré et al (2008) identified a set of early 'tectonomagmatic' domes on the Norwegian margin, which are of Late Cretaceous -Paleocene age and related to break-up magmatism.…”
Section: Norwegian Marginmentioning
confidence: 99%
“…1) (e.g. Doré et al 2008;Ritchie et al 2008;Tuitt et al 2010), although there is also evidence of earlier compression Tuitt et al 2010;Lundin et al 2013). The aim of this paper is to use results from the NAG-TEC project to examine the relationship between the siting of the post-break-up compressional structures and the morphology and rheology of the margin established as a consequence of the preceding extensional history.…”
mentioning
confidence: 99%